Occurrence of cluster structures in knowledge-intensive services - Esther Schricke (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
The aim of this article was to investigate how far clusters in knowledge-intensive service industries have developed and what kind of agglomeration advantages they generate. Therefore the first step was to analyse which knowledge-intensive service industries exhibit spatial concentration. Based on this analysis, the absolute as well as the relative concentrations in these industries was examined at the NUTS 3 level. The results show that cluster structures have developed in some but not all knowledge-intensive industries of the service sector. A high measure of spatial concentration does not necessarily mean that a cluster exists, since especially in less urban region high localisation quotients are frequently ascribed to either one company or only a small number of companies. The knowledge-intensive services with cluster structures differ with regard to external effects, each of which becomes important: a highly qualified labour pool is by definition important for all knowledge-intensive industries of the service sector and fundamental for the existence of cluster structures in each of the examined services. Nevertheless there are however crucial differences regarding the significance of further external effects. Porter-externalities do not appear to stimulate competiveness in any of the examined industries of the service industry. However, none of the available studies explicitly examined the aspect of competition. Thus the interplay of agglomeration advantages needs to be researched further. The type of knowledge and the market environment should also be regarded as important factors (Orsenigo 2006: 201). Contact to local suppliers and customers in industries that are characterized by project work, such as the film and television industry or the media, are particularly important. Supporting clusters and networks is currently fashionable and is practised by different actors. The results show that cluster and network policies have to be focussed on the field of activity. It seems in any case sensible to expand the knowledge and education infrastructure in knowledge-intensive services which do not have cluster structures. The spatial proximity of actors in the innovation process or of suppliers and customers is not always advantageous. Too strong a focus on spatially concentrated exchange processes, leading to an isolation from global trends, can prove to have negative effects in the long term. In this respect the great importance of a qualified labour pool provides a starting point for policy measures that could also be useful for other fields of activity. This includes the development and financing of (partially specialised) educational institutions or measures. The appeal of the surroundings is also important to tie highly qualified staff to a region, as the discussion on a creative class (Florida 2002; 2005) also shows. While factors such as urbanity can hardly be influenced politically, there are certain initiatives regions can adopt to compensate for the lack of attractiveness. In regions where companies find it difficult to attract qualified staff from other regions higher education institutions are important sources of qualified staff. Therefore increasing the attractiveness of higher education institutions and of relevant study programmes are a first starting point. Likewise, the example of ITsax shows how companies can cooperate successfully in the area of recruitment. Furthermore, the provision of childcare facilities or international schools is important for the creation of attractive conditions particularly for women and / or international employees.
urn:nbn:de:0011-n-2281372
Keywords: 330